Moving to Opportunity : Successful Integration or Bright Lights? - Lall, Somik V. (Washington, DC: World Bank, 2012)
Economists have long argued that migration decisions are motivated by the possibility of earning higher wages. But since many migrants don't find jobs after moving, is this attraction irrational? This paper, using census data from Brazil, examines the causes and consequences of internal migration. It finds that many poor/ uneducated people are pushed to migrate as they do not get access to basic services such as health care and clean water in their hometowns, and these migrants have lower chances of assimilating into destination labor markets. Policies that improve human capital and social services in lagging regions are likely to be useful for individual migrants.